2002
DOI: 10.1200/jco.2002.20.6.1449
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Soy Phytoestrogens on Hot Flashes in Postmenopausal Women With Breast Cancer: A Randomized, Controlled Clinical Trial

Abstract: The soy beverage did not alleviate hot flashes in women with breast cancer any more than did a placebo. Future research into other compounds is recommended to identify safe and effective therapies for hot flashes in breast cancer survivors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(58 citation statements)
references
References 31 publications
4
48
0
2
Order By: Relevance
“…In this study, there were no significant effects on hot flash frequency or severity in either the soy or flax group (Lewis et al, 2006). Another randomized doubleblind controlled trial performed in 72 breast cancer patients who consumed 70 mg isoflavones/day or placebo for 12 weeks showed no significant effects of the isoflavones (MacGregor et al, 2005), consistent with other trials performed in breast cancer patients (Quella et al, 2000;Van Patten et al, 2002). These last studies suggest that breast cancer patients may respond differently to soy than healthy controls, particularly if they are on treatments such as tamoxifen or hormone inhibitors.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, there were no significant effects on hot flash frequency or severity in either the soy or flax group (Lewis et al, 2006). Another randomized doubleblind controlled trial performed in 72 breast cancer patients who consumed 70 mg isoflavones/day or placebo for 12 weeks showed no significant effects of the isoflavones (MacGregor et al, 2005), consistent with other trials performed in breast cancer patients (Quella et al, 2000;Van Patten et al, 2002). These last studies suggest that breast cancer patients may respond differently to soy than healthy controls, particularly if they are on treatments such as tamoxifen or hormone inhibitors.…”
Section: Discussionsupporting
confidence: 91%
“…In order to overcome this, recent meta-analyses have been published that select out the very best trials, using specific pre-defined criteria, and pool the studies into one analysis in order to M. S. Kurzer Inflammopharmacology increase statistical power. One recent meta-analysis of 12 randomized, controlled trials (Murkies et al, 1995;Albertazzi et al, 1998;Scambia et al, 2000;Upmalis et al, 2000;Knight et al, 2001;St Germain et al, 2001;Faure et al, 2002;Han et al, 2002;Van Patten et al, 2002;Burke et al, 2003;Penotti et al, 2003;Colacurci et al, 2004) reported that isoflavone supplementation was associated with a reduction in hot flashes of 34 % (95 % confidence intervals -0.47 to -0.21, P<0.0001), with an increase in efficacy as the baseline number of flashes and isoflavone dose increased (Howes et al, 2006) (Fig. 1).…”
Section: Discussionmentioning
confidence: 83%
“…Randomized trials of soy products vs placebo in this patient population failed to demonstrate a significant improvement in hot flash symptoms [22,23] Similar results were reported from a study randomizing breast cancer patients to black cohosh or placebo [24].…”
Section: Complementary and Alternative Medicinementioning
confidence: 53%
“…Results of investigations of soy protein, a prominent source of phytoestrogen, for the treatment of hot fl ashes have been mixed but suggest that soy protein and isolated isofl avones do not reduce symptoms [17]. Furthermore, the long-term safety of pharmacologic doses of soy in patients with a history of breast or uterine cancer is not established.…”
Section: Alternative Therapiesmentioning
confidence: 93%